Expression of HSF1 and GDF9 Genes in Bovine Oocytes Supplemented with Follicular Fluid Exosomes During in vitro Maturation - Prathima, Perneti; Abhilash, R S; Jayakumar, Choppillil; Aravind, Amritha; Venkatachalapathy, Ramalingam Thirupathy; Kurian, Elizabeth; Priya, Melepat; Kumar, Parvathi Prem (The Indian Journal of Animal Reproduction, 2025)
The efficiency of embryo production using in vitro technologies in cattle remains suboptimal, with a substantial pro portion of female gametes failing to develop after in vitro manipulation. As oocyte quality critically influences embryo development, identifying genetic markers to predict oocyte competence is vital. Follicular fluid-derived exosomes, which contain biomolecules that influence gene expression in oocytes, which enhances the oocyte developmental competence. This study, evaluated 318 culture-grade cumulus-oocyte complexes (COCs) collected from slaughterhouse ovaries and subjected them to in vitro maturation (IVM) under two groups. Group I (control) comprised 160 oocytes matured under standard physiological conditions (38.5°C) for 24 h, while Group II included 158 oocytes matured with follicular fluid exosome supplementation. Both groups were incubated in a controlled environment with 5 per cent CO2 and 95 per cent relative humidity. The cumulus expansion rates were 92.73 ± 4.42% in Group I and 94.05 ± 2.62% in Group II, while polar body extrusion rates were 8.97 ± 2.72% and 10.98 ± 2.50%, respectively. Gene expression analysis revealed a significant down regulation of HSF1 (fold change: 0.84, p ≤ 0.05) in Group II, whereas GDF9 showed an upregulation (fold change: 1.56), though not statistically significant. The findings suggest follicular fluid exosome supplementation may enhance oocyte maturation under invitro conditions.
Keywords: Bovine oocyte; Oocyte maturation; Exosome; 1 and GDF9